Design Exploration of Bamboo Shells Structures by Using Parametric Tools - María Guadalupe Estrada Meza; Edwin González Meza; Doris Abigail Chi Pool; Jaqueline Sofía McNamara Trujillo (Applied Sciences, 2022)
Bamboo is a promising material for structural use due to its mechanical properties and rapid growth. Currently, standards and codes to support the analysis and calculation of bamboo structures are still scarce. Even international standards do not include specifications for the design of complex geometries. This work aimed to verify the use of parametric tools to design complex shapes. First, the NSR-10 Colombian code was used to analytically solve and design the mechanical behavior of double-curved shells. Then, the results were compared to those calculated with the add-on Karamba3D. Lastly, verification was considered successful when both results coincided. Here, it should be noticed that the resultant data might lead to plastic deformation of the cylinder head. However, this work did not intend to formulate structural designs whose beams effectively support the requested stresses but focused on the verification of software applications. Once the software was verified, this work further analyzed the structural behavior of two double curvature geometries simulated with bamboo, showing that digital simulation tools have the potential to be applied during the early structural design phases.